2017
DOI: 10.3389/fncom.2017.00044
|View full text |Cite
|
Sign up to set email alerts
|

Potential Mechanisms and Functions of Intermittent Neural Synchronization

Abstract: Neural synchronization is believed to play an important role in different brain functions. Synchrony in cortical and subcortical circuits is frequently variable in time and not perfect. Few long intervals of desynchronized dynamics may be functionally different from many short desynchronized intervals although the average synchrony may be the same. Recent analysis of imperfect synchrony in different neural systems reported one common feature: neural oscillations may go out of synchrony frequently, but primaril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(44 citation statements)
references
References 26 publications
2
42
0
Order By: Relevance
“…Earlier studies showed that one can change parameters of oscillators in such a way that the distribution of desynchronization duration is changed independently of the average synchrony strength (e.g., Ahn et al, 2011;Rubchinsky et al, 2014;Ahn and Rubchinsky, 2017). In the coupled ecological oscillators considered here, changes in the temporal patterning of synchronization can be independent of the synchronization strength too, as evidenced by the results presented above (although they may co-vary together as well).…”
Section: Changing Desynchronization Durations Independently Of Frequesupporting
confidence: 55%
“…Earlier studies showed that one can change parameters of oscillators in such a way that the distribution of desynchronization duration is changed independently of the average synchrony strength (e.g., Ahn et al, 2011;Rubchinsky et al, 2014;Ahn and Rubchinsky, 2017). In the coupled ecological oscillators considered here, changes in the temporal patterning of synchronization can be independent of the synchronization strength too, as evidenced by the results presented above (although they may co-vary together as well).…”
Section: Changing Desynchronization Durations Independently Of Frequesupporting
confidence: 55%
“…Synchronous states are more prominent during slow-wave sleep and anesthesia whereas asynchronous firing activity is prevalent in the states of wakefulness and REM sleep (Steriade et al 2001 ; El Boustani et al 2007 ; Greenberg et al 2008 ; Sanchez-Vives et al 2017 ). Notably, the degree of synchrony in cortical and subcortical regions varies with time, often with intermittent switches between synchronous and asynchronous states (Ahn and Rubchinsky 2013 , 2017 ; Hahn et al 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dynamics of the non-plastic variant of this system was studied in Ahn and Rubchinsky (2017). Based on that study, we vary values of three parameters of the potassium current in such a way as to change the dynamics of the non-plastic network from exhibiting predominantly short desynchronizations (i.e., those observed in experiments) to one with a large mode of desynchronization durations.…”
Section: Resultsmentioning
confidence: 99%